Bolivia 2006: reforma estatal y construcción del poder - Deheza, Grace (Revista de Ciencia Política, 2007)
2006 marked a new era in Bolivian history. For the first time, an aymaran origin leader constitutionally assumed the country’s Presidency. Throughout this year, President Evo Morales Ayma emitted policies to reform the State and recover the control of Bolivia’s natural resources. The process of changing the Bolivian political Constitution started with the creation of a Constituent Assembly and an autonomic referendum, parallel processes that until today, are still redefining the country’s new political - administrative configuration.